Knowledge of and challenges experienced by health workers managing maternity patients in primary health care(PHC) clinics of Yobe State, Nigeria - Ali, Abdullahi Danchua (My University, 2014)
This study, entitled “Knowledge of and challenges of health workers managing maternity patients at PHC facilities of Yobe State, Nigeria,” had the following objectives:  To describe the socio-demographic characteristics of the health workers in the Primary health care (PHC) facilities in the state.  To determine the level of knowledge of the health workers regarding the management of maternity patients in Primary health care facilities in Yobe State.  To determine the challenges experienced by the health workers in the Primary health care facilities in the state. The study was primarily aimed at exploring the health workers level of knowledge, skills and competencies in the management of maternity patients and their contributions towards the control and reduction of maternal mortality in the state. METHODS: A cross sectional survey study in PHC clinics of six selected local government areas of the state, namely Gujba, Geidam, Fune, Fika, Nguru and Jakusko local government areas. A total of 221 health workers (n=221) were interviewed using structured questionnaires, whilst 46 facility managers (n=46) were given self-administered questionnaires while on duty, and data were collected concurrently from clinic records. The data were cleaned, entered in to Epi info statistical software, imported and analysed using STATA. Descriptive and inferential statistics were used to interpret the outcomes of the analysis. RESULTS: More than half of the respondents were female (65.61%) with an average age of 33 years (SD± 8.1). Categories of the health workers who participated in the study were SCHEW, JCHEW, SSCE, TBAS, EHA/EHO and others who were not trained in any form as health workers, but were found running the affairs of maternity patients. More than 80% of the clinics did not have functional ambulances and there was gross inadequacy of basic services in most of the clinics; only 14 out of 46 clinics had portable water supply and electricity. There was a large seasonal turnout of patients in the clinics but poor patronage by maternity clients. The health workers in the maternity unit were found to be deficient in the knowledge, skills and competencies to manage maternity patients. Protocols were not followed (68.78%), some significant information about ante-natal care was not given to v clients and maternity clients were not adequately informed of some of the danger signs of pregnancy. There was a poor standard of institutional deliveries and the majority of the Health Workers had no training on EOC or conducting a clean and safe delivery. CONCLUSION: Examining the background of the current health workers in the primary health care facilities, the attainment of MDG 5 by 2015 will not be a reality, unless urgent measures are put in place, including large recruitment and motivation midwives, and deployment of these midwives to the rural health clinics. There is a need for the existing health workers to be supported by government and enrolled in short course training in Colleges of Midwifery to acquire the much needed skills and competencies for the care of maternity patients.
A research report submitted to the Faculty of Health Science, in partial fulfillment of the requirement for the award of a Master’s Degree in Nursing Sciences by the Witwatersrand University of Johannesburg, South Africa.
Keywords: Child Mortality; Maternal Health